Nonlinear mechanisms of the exchange rate pass-through: A Phillips curve model with threshold for Brazil - Correa, Arnildo da Silva (2010)
This paper investigates the presence of nonlinear mechanisms of the pass-through from exchange rate to inflation in Brazil. In particular, it estimates a Phillips curve with a threshold for the pass-through. The paper examines whether the short-run magnitude of the pass-through is affected by the business cycle, direction and magnitude of the exchange rate change, and volatility of the exchange rate. The results indicate that the short-run pass-through is higher when the economy is booming, when the exchange rate depreciates above some threshold and when the exchange rate volatility is lower.